Clinical and Socio demographic profile of attendees at ART centre in a tertiary care hospital in Mangalore, India - Nayak, U.B.; Lenka, S.; Achappa, B. (Asian Journal of Medical Sciences, 2015)
Introduction: India has the third largest number of people living with HIV/AIDS. There is a need to study the profile of patients who come to ART centers and link their clinical and socio-demographic variables in the management. Moreover, it is important to understand the presentation of HIV disease in the local context and culture. The present study is aimed at identifying the socio-demographic characteristics, clinical presentations of HIV/AIDS patients, opportunistic infections and the possible risk factors for acquiring HIV infection at an ART centre of Government Wenlock hospital, situated in Karnataka state of India. Materials and Methods: In this study 102 HIV patients attending the HIV clinic were enrolled and they were followed for a period of one year with relevant investigations. Results: Of 102 patients 69 were males and 33 were females.The mean age of the study subjects at the time of diagnosis was 38.06. Heterosexual contact was the commonest mode of transmission in96 (94.12%) patients. History suggestive of a risk factor for HIV transmission could not be elicited in 4 (3.92%) patients. Fever (71.5%), weight loss (62.74%), cough (51.96%) and chronic diarrhea (43.9%) were the common presenting symptoms. The most common opportunistic infection was oral candidiasis (66.67%) followed bytuberculosis (22.54%) and pneumocystis pneumonia (13.72%). Significant number of patients (30.37%) developed Zidovudine induced anemia and females were more prone for Zidovudine induced anemia as compared to males. CD4 counts of the patients were significantly inversely correlated with the number of symptoms and the number of opportunistic infections. Conclusion: Majority of patients were of low socioeconomic status and in productive age group with heterosexual contact being commonest mode of transmission.Significant number of patients developed Zidovudine induced anemia and females were more prone. DOI: http://dx.doi.org/10.3126/ajms.v6i5.11622 Asian Journal of Medical Sciences Vol.6(5) 2015 61-65